Heavy metal bioremediation using microbially induced carbonate precipitation: Key factors and enhancement strategies - Zhang, Wenchao; Zhang, Hong; Xu, Ruyue; Qin, Haichen; Liu, Hengwei; Zhao, Kun (Frontiers in Microbiology, 2023)
With the development of economy, heavy metal (HM) contamination has become an issue of global concern, seriously threating animal and human health. Looking for appropriate methods that decrease their bioavailability in the environment is crucial. Microbially induced carbonate precipitation (MICP) has been proposed as a promising bioremediation method to immobilize contaminating metals in a sustainable, eco-friendly, and energy saving manner. However, its performance is always affected by many factors in practical application, both intrinsically and externally. This paper mainly introduced ureolytic bacteria-induced carbonates precipitation and its implements in HM bioremediation. The mechanisms of heavy metal immobilization and in-situ application strategies (that is, biostimulation and bioaugmentation) of MICP are briefly discussed. The bacterial strains, culture media, as well as HMs characteristics, pH and temperature, etc. are all key factors that control the success of MICP in HM bioremediation. The survivability and tolerance of ureolytic bacteria under harsh conditions, especially in HM contaminated areas, have been the bottleneck for an effective application of MICP in bioremediation. The effective strategies for enhancing tolerance of bacteria to HMs and improving the MICP performance were categorized to provide an in-depth overview of various biotechnological approaches. Finally, the technical barriers and future outlook are discussed. This review may provide insights into controlling MICP treatment technique for further field applications, in order to enable better control and performance in the complex and changeable environmental systems.